Evaluation of the machining of a batch of parts by the turning process in carbon steels and cast iron (2018)
In the present investigation, the effect of main parameters for the development of parts in production such as feed rate and depth were evaluated, obtaining the machining costs depending on the characteristics of the material. The machining process used was that of turning in pieces with carbon steels and cast iron as the base material, varying the feed rate in a range between 0.2mm/tooth and 0.8mm/tooth and the depth between 1mm and 4mm allowing important parameters to be determined such as cutting speed and machine operating conditions to obtain a good final finish without affecting the surface of the piece and in production time required to optimize costs.